8(x+4)=7(2x+3)

Simple and best practice solution for 8(x+4)=7(2x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+4)=7(2x+3) equation:


Simplifying
8(x + 4) = 7(2x + 3)

Reorder the terms:
8(4 + x) = 7(2x + 3)
(4 * 8 + x * 8) = 7(2x + 3)
(32 + 8x) = 7(2x + 3)

Reorder the terms:
32 + 8x = 7(3 + 2x)
32 + 8x = (3 * 7 + 2x * 7)
32 + 8x = (21 + 14x)

Solving
32 + 8x = 21 + 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
32 + 8x + -14x = 21 + 14x + -14x

Combine like terms: 8x + -14x = -6x
32 + -6x = 21 + 14x + -14x

Combine like terms: 14x + -14x = 0
32 + -6x = 21 + 0
32 + -6x = 21

Add '-32' to each side of the equation.
32 + -32 + -6x = 21 + -32

Combine like terms: 32 + -32 = 0
0 + -6x = 21 + -32
-6x = 21 + -32

Combine like terms: 21 + -32 = -11
-6x = -11

Divide each side by '-6'.
x = 1.833333333

Simplifying
x = 1.833333333

See similar equations:

| 5(x-4)-3(x-2)=12 | | 2a-17=21 | | 0.22(x+9)=0.2x+3.6 | | =(2x)(3x+1) | | -2w+8-2w=-w-7w+3w | | 0=(2x)(3x+1) | | 39.95+.35m=69.70 | | 2x+3x=2x-4 | | -8-(12-16)= | | 7a-(3a-4)=16 | | (-3)(2)(-1)(-3)= | | 6-c=16 | | -f+300=-65 | | x^2+3xy-8x-4y= | | 14(b-955)=616 | | F(10)=2x+5 | | 3+-7=4t+7 | | 2m-1=-6m+8 | | -2+10m-10=8(3m+4)-2 | | 49=3(x-3)+4x-1+2x+5 | | 24k=8(x+6) | | 3t^2-20t=-12 | | n=18+m | | 8.25c+12(55-c)=585 | | -5=7+3y | | 6x-13=83 | | 3+-7=4(t+7) | | x^2+x+120=0 | | 3x+50=275 | | -6(-6r+2)=-40+8r | | x+a^4=81a^4 | | F(n)=2n+2 |

Equations solver categories